Holistic Human Resource Development Model: The Inclusion Of Spiritual Quotient And The Influence Of Islamic Teachings - Mahmood, Arshad (2018)
Employees are the most valuable assets in organisations. HRD programmes aim to improve the development of employees and organisational effectiveness. HRD programmes help employees to develop their personal and organisational skills for organisational effectiveness. The conventional strategy of organisations in nurturing their employees focuses on enhancing an individual’s knowledge, skills, and abilities (intelligence quotient) and emotional control (emotional quotient). However, despite this immense interest in human capital, organisations tend to fall short of a holistic approach to human resource development which eventually affects their performance.